Pyridyl‐Endcapped Polyynes: Stabilized Wire‐like Molecules. Issue 47 (26th October 2016) - Krempe, Maximilian; Lippert, Rainer; Hampel, Frank; Ivanović‐Burmazović, Ivana; Jux, Norbert; Tykwinski, Rik R.
Abstract: A 4‐ethynylpyridyl derivative with sterically shielding phenyl groups in the 3‐ and 5‐positions has been synthesized and used to terminate a series of polyynes. This approach allows for the synthesis of stable polyynes up to an octayne, twice as long as previous accessible for "unstabilized" pyridyl‐endcapped polyynes. The potential of these polyynes as wire‐like linkers to metal centers is demonstrated by axial coordination of pyridyl groups to zinc‐ and ruthenium‐metalloporphyrins. Abstract : Protective phenyl groups : A synthetic route to the longest known pyridyl‐endcapped polyynes is developed. The wire‐like molecules are stabilized through steric shielding from pyridyl substituents, and the polyynes serve as molecular wires through endcapping with either Zn‐ or Ru‐porphyrins via axial coordination.